ANALYSIS OF PERSONAL SELLING STRATEGIES IN INCREASING NEW STUDENT ADMISSIONS AT STIKes ABDI NUSANTARA - Putri Ulfa Eriza; Punkie Paramita Dewi (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze personal selling strategies in increasing new student admissions at STIKes Abdi Nusantara using a qualitative approach through data collection techniques consisting of interviews, observations, and document studies. The findings indicate that personal selling strategies are implemented through various approaches, such as school visits, communication via WhatsApp, participation in campus fairs, and the involvement of lecturers, staff, active students, and alumni, which create two-way communication and build emotional closeness with prospective students. This strategy has a positive impact on increasing the number of applicants, supported by the responsiveness of the promotional team, the appropriate use of media, and alumni testimonials. Although several obstacles were identified, including limited promotional personnel and low initial responses from prospective students, the institution was able to adapt its strategies effectively. Therefore, personal selling is considered an effective and relevant promotional strategy in higher education marketing.